Layanan Bimbingan Kelompok Teknik Home Room Untuk Meningkatkan Sikap Anti Seks Bebas - Farid Hidayat; Edris Zamroni; Sucipto Sucipto (Universitas Muria Kudus, 2018)
The purpose of this study are: 1) Describe the implementation of group guidance services with homeroom techniques to improve anti-sex free attitudes in class XI TAV 2 students SMK Negeri 2 Kudus, 2) Know the increase in anti-sex free attitudes through group guidance services with homeroom techniques for class students XI TAV 2 of SMK Negeri 2 Kudus. Type of Research PTBK with stages: 1. Planning, 2. Implementation, 3. Observation, and 4. Reflections carried out in 2 cycles of research, each cycle carried out three meetings. Data analysis used is descriptive qualitative data analysis. The results of the study were pre-cycle conditions. The number of free anti-sex attitudes of 8 students of class XI TAV 2 of SMK Negeri 2 Kudus was 133 with a percentage of 42% in the very poor category, at the end of the first cycle the score of anti-free sex was 202 with percentage 63% in the less category and at the end of the second cycle the number of anti-sex free attitudes from 8 students of class XI TAV 2 of SMK Negeri 2 Kudus was 263 with a percentage of 82% in the good category. Selin also concluded that the hypothesis of action that researchers made in chapter II which reads Homeroom Technical Guidance Service Group can increase the anti-free attitude of students of class XI TAV 2 of SMK Negeri 2 Kudus, declared acceptable.